Maternal and Fetal Outcome in Emergency versus Elective Caesarean Section - Darnal, Naveen; Dangal, Ganesh (Journal of Nepal Health Research Council, 2020)
Background: Caesarean section is one of the most performed surgical procedures all over the world. It is associated with high morbidity and mortality as compared to vaginal delivery. The present study was carried out to evaluate the maternal and neonatal outcome and complications in two groups of pregnant women who underwent elective and emergency cesarean section, so that measures can be taken to reduce morbidity and mortality in near future.Methods: It was hospital based descriptive cross-sectional study carried out at Paropakar Maternity and Women’s Hospital from October to December 2018. There were 340 patients enrolled in the study 170 in elective and 170 in emergency caesareans selected randomly. Ethical approval was obtained from the Institutional Review Board and informed consent was taken from the patients and patients’ guardians. Data were collected daily from the Operation Theater. Results: The rate of caesarean section in the hospital was 30.7%. Proportion of emergency caesarean section was 1324 (74.4%) and elective caesarean section was 456 (25.6%). Emergency Caesarean section was more common in younger age group and in primigravida while elective Caesarean section was more common in advanced age group and in multigravida. The most common indication for emergency Caesarean section was Fetal Distress and the most common indication for elective Caesarean section was previous cesarean with refused vaginal delivery after cesarean section. The maternal outcome in terms of post-operative wound infection, (post-partum hemorrhage, urinary tract infection need for blood transfusion, fever and need for maternal intensive care unit admission was significantly (p- value <0.05) higher in emergency Caesarean section than in elective Caesarean section .The fetal outcome in terms of birth asphyxia, meconium stained liquor and need for Neonatal ICU admission were significantly (p – value <0.05) higher in emergency Caesarean section than in elective Caesarean section. Conclusions: Maternal and fetal complications were significantly higher in the emergency caesarean section as compared to elective caesarean section group.Keywords: Fetal outcome; emergency cesarean section; elective cesarean section; maternal outcome.